Eksperimen Pembelajaran Matematika Dengan Strategi Problem Based Learning Dan Discovery Learning Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Pada Siswa Kelas VII SMP Muhammadiyah 1 Surakarta Tahun 2015/2016 - RAHMAWATI, FITRIYANA; , Drs. Slamet HW, M.Pd (2017)
This study aimed to describe and analyze: (1) the effect Problem Based Learning and Discovery Learning in mathematics learning outcomes, (2) effects motitation in mathematics learning outcomes, (3 interaction Problem Based Learning and Discovery Learning and motivation in mathematics learning outcomes. Type of the research is experiment with quasi experimental design. The research was conducted students of VII Grade of SMP Muhammadiyah 1 Surakarta of even semester of academic year 2015/2016 with the population all students of VII. The class sample of research by using the strastified cluster random sampling. Methods of data collection use documentation and test. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is Problem Based Learning and Discovery Learning in mathematics learning outcomes with Fa=17,58(2) there is effects motivaton in mathematics learning outcomes with Fb=22,93(3) there is no interaction Problem Based Learning and Discovery Learning in mathematics learning outcomes in terms motivation with Fab=0,17 .